Hubungan Pengetahuan Dengan Pelaksanaan Discharge Planning Di Ruang Rawat Inap RSUD Kota Dumai Riau - Rina Fitriani; Hafni Bachtiar; Esthika Ariany Maisa (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Discharge planning is a process that begins with the patient receiving health services followed by continuity of care both in the healing process and in maintaining the degree of health until the patient feels ready to return to his environment, and is also an important part of the implementation of nursing care. With the discharge planning can reduce the days / length of patient care, prevent recurrence, improve the patient's health condition and reduce mortality and morbidity. This study aims to determine the relationship between knowledge and the implementation of discharge planning in the inpatient room of Dumai Hospital. The design of this study was cross sectional using the Chi square test. The sample consisted of 96 nurses. The sample technique used is proportional stratified random sampling. The results showed that most of the nurses were not good at discharge planning, namely 72.9%. Most of the nurses' knowledge was not good, namely 89.6%. The results of the analysis test showed that there was no significant relationship between the knowledge factor and the implementation of discharge planning (p = 0.199).